(untitled) (European Journal of Pure and Applied Mathematics, 2024)
Our main purpose is to introduce the concepts of upper and lower s-(τ_1,τ_2)p-continuous multifunctions. Furthermore, several characterizations of upper and lower s-(τ_1,τ_2)p-continuous multifunctions are investigated.